Health-related-out-of-pocket expenditures, their distribution and determinants among patients undergoing dialysis at Teaching Hospital Jaffna - Krishanth, M.; Kanisdija, K.; Devindani, T.K.S.; Sankalpana, H.; Azhar, A.; Kumar, R.; Brammah, T. (Faculty of Medicine, University of Jaffna, 2024)
Background and objectives: Chronic kidney disease (CKD) is a significant public health issue in Sri Lanka, leading to kidney failure and the need for dialysis. Limited dialysis facilities result in patients suffering out-of-pocket expenses (OOPE) on healthcare. This research aims to investigate health-related OOPE, their distribution and determinants among patients undergoing dialysis at Teaching Hospital Jaffna (THJ). Methods: This hospital-based descriptive cross-sectional study was conducted among patients registered for dialysis at THJ (November 2022 - February 2023). Data were collected with an interviewer- administered questionnaire from all patients who matched the study criteria. Statistical analysis was performed using SPSS (v20). Standard descriptive statistics were used along with Kruskal-Wallis and Mann-Whitney U tests to test for differences in OOPE based on socio-demographic factors (critical level 0.05). Results: Among 92 participants, 70.7% were male and 68.7% were >40 years of age. Half the sample (50%) had O/L education or beyond, and the majority lived >10 km away from THJ (56.5%) and received no financial assistance (60.9%). Mean and median total monthly health-related OOPE in government and private sectors was LKR 10,949.34 and LKR 8650.00, respectively. The highest OOPE were incurred in the course of accessing the free dialysis services available in the public sector, amounting to a mean and median OOPE of LKR 5389.67 and 3000.00, respectively, spent mainly on transport (mean LKR 2278.37, median LKR 1550), laboratory tests in the private sector (mean LKR 1359.02, median 0) and meals (mean LKR 886.52, median LKR 800.00). None of the participants used the private sector for dialysis; channeling incurred the highest expenses in the private sector (mean LKR 1864.67, median 0), mainly on tests (mean LKR 543.48, median 0), medicines (mean LKR 523.91, median 0) and transport (mean LKR 425.54, median 0). OOPE varied significantly by age, marital status, employment and whether receiving financial assistance (p≤0.05). The elderly, unmarried, unemployed and those receiving financial assistance incurred more OOPE on healthcare. Conclusion and recommendations: Patients spend substantial amounts on transport, tests and meals in the course of accessing dialysis services at THJ. While most patients do not receive financial assistance, the CKD allowance provided by the government is inadequate to cover health-related OOPE. Strengthening government sector dialysis facilities and providing more financial support for patients is recommended.
Keywords: Chronic kidney disease; Dialysis; Out-of-pocket expenditure; Health systems